STRUCTURAL OPTIMIZATION OF AGRO-INDUSTRIAL HAMMER MILL BLADES BASED ON FINITE ELEMENT SIMULATION AND EXPERIMENTAL VALIDATION - Ragil Indrawati; Farika Tono Putri; Wahyu Isti Nugroho; Eni Safriana; Rizkha Ajeng Rochmatika; Haffiyan Faza Rizaldy; Ilham Syaifullah; Mohammad Afiq Haidar; Muhammad Haikal Firmansyah; Aden Suhaedi; Ananda Ihza Indrawan; Arya Ramadhan C. S.; Reza Nur Irsandi (Journal of Economic, Business and Engineering (JEBE), 2026)
Hammer mills are widely used for grinding agroindustrial materials. However, suboptimal blade geometry and sieve selection often lead to excessive stress concentration, premature wear, and uneven particle size distribution. This study aims to optimize hammer mill blade design using the Finite Element Method (FEM) and to validate the best-performing design through experimental tests with sieve diameters of 3 mm, 4 mm, and 5 mm. Three blade designs were numerically analyzed at a rotor speed of 2700 rpm under a cutting force of 31,392 N, evaluating von Mises stress, displacement, strain, and factor of safety. Simulation results indicated that Design 1 exhibited the lowest stress, displacement, and strain, along with the highest factor of safety, demonstrating optimal structural stability and fatigue resistance. Experimental validation revealed that a 4 mm sieve provided the best balance between throughput, energy efficiency, and minimal material loss. The developed hammer mill operated stably with a capacity of 21 kg/h and reliable mechanical performance. The integration of FEM-based optimization and experimental validation offers a robust scientific framework for developing low-cost, high-performance agroindustrial grinding systems, while supporting sustainable production through reduced energy consumption and material waste, in alignment with SDG 2 (Zero Hunger) and SDG 12 (Responsible Consumption and Production). Future research may explore rotor geometry optimization for various feedstocks and the implementation of adaptive speed control to further enhance energy efficiency.